Refugee Resettlement - Katsunori Ohta; Yuji Tamura (Global Labor Organization (GLO), 2023)
Resettlement is one means of assisting refugees to regain self-reliant living with- out constant fear. The global total of resettled refugees has remained fractional relative to the need. To contribute to the ongoing effort to increase resettlement, we consider self-enforceable sharing of full resettlement through analysis of a repeated game at the beginning of which host countries bargain over their shares. We find that cooperation opportunities are diminished, or else lost, by cutting the cost of resettlement, whereas they are expanded by heightened pureness in treating refugee protection as a humanitarian public good. Our finding thus makes us reconsider the implications of static-game analysis that both high cost and public-good nature of refugee protection are the sources of insuffi cient admission. We also show that a wide range of cooperation opportunities may not be conducive to the effi ciency of an equilibrium outcome because it allows the bargaining outcome to deviate from the effi cient one. We suggest policies for creating cooperation opportunities and improving equilibrium effi ciency. Our framework is suffi ciently general and is useful for examining other similar problems of public-good provision.
Keywords: H41; H87; 330; International cooperation; International public good; Noncooperative game; Repeated game; Alternate-offer bargaining